Comparison of evapotranspiration estimates using the water balance and the eddy covariance methods - Denager, T. (2020)
Evapotranspiration from eddy covariance (ETEC) is cross‐checked with evapotranspiration calculated as the residual of the water balance (ETwb). The water balance closure using ETEC is simultaneously validated. Over a 6‐yr period, all major terms of the water balance are measured including precipitation, recharge from percolation lysimeters, and soil moisture content from a cosmic‐ray neutron sensor, a capacitance sensor network, and time domain reflectometry (TDR), respectively. In addition, we estimate their respective uncertainties. The study demonstrates that both monthly and yearly ETEC and ETwb compare well and that the water balance is closed when ETEC is used. Concurrently, incoming available energy (net radiation minus ground heat flux) on average exceeds the turbulent energy fluxes (latent heat flux and sensible heat flux) by 31%, exposing the energy–surface imbalance. Consequently, the imbalance in the energy balance using the eddy covariance method must, to a lesser degree, be caused by errors in the latent heat estimates but can mainly be attributed to errors in the other energy flux components.